Convergence Across Polish Regions, 2005–2011 - Piętak, Łukasz (Comparative Economic Research. Central and Eastern Europe, 2015)
This article analyses the convergence across Polish regions between 2005-2011. Its theoretical and empirical character determined the choice of research methods. The theoretical part includes an analysis of the literature devoted to the convergence theory, and the empirical part is based on statistical surveys. Statistical data used in the article was taken from the following databases: for the United Kingdom - Office for National Statistics; for Finland - Statistic Finland; for Poland and the rest of the countries - Statistical Yearbook of the Regions - Poland from 2005 to 2013. The studies confirmed that in Poland a strong concentration of economic activity took place in analyzed period. The convergence of per capita GDP did not apply. Rich regions grew faster than poor ones. The convergence of labour productivity did not apply either. The divergence of the K/L relation determined the divergence of labour productivity in the analyzed period. In the last part of the article the author analyzed the convergence across regions in EU countries. In case of countries that gained the accession to the EU on 1 May 2004, convergence did not apply. On the other hand, rich countries of EU like Austria, Belgium or the Netherlands confirmed the phenomenon of convergence at the NUTS level in analyzed period.